Optimising implementation of telehealth in oncology: A systematic review examining barriers and enablers using the RE-AIM planning and evaluation framework. (December 2022) - Bu, Stella; Smith, Allan 'Ben'; Janssen, Anna; Donnelly, Candice; Dadich, Ann; Mackenzie, Lisa J.; Smith, Andrea L.; Young, Alison L.; Wu, Verena S.; Smith, Sarah J.; Sansom-Daly, Ursula M.
Abstract: Telehealth facilitates access to cancer care for patients unable to attend in-person consultations, as in COVID-19. This systematic review used the reach, effectiveness, adoption, implementation, and maintenance (RE-AIM) framework to evaluate telehealth implementation and examine enablers and barriers to optimal implementation in oncology. MEDLINE, PubMed, CINAHL, and the Cochrane Database of Systematic Reviews were searched between January 2011-June 2022. Eighty-two articles representing 73 studies were included. One study explicitly used the RE-AIM framework to guide study design, conduct, or reporting. Reach (44%) and implementation (38%) were most commonly reported, maintenance (5%) least commonly. Key telehealth implementation enablers included professional-led delivery, patient-centred approaches, and positive patient perceptions. Key barriers included patient discomfort with technology, limited supporting clinic infrastructure, and poor access to reliable internet connection and videoconferencing. While a patient-centred and professional-supported approach enables telehealth implementation, technology and infrastructure constraints need surmounting for sustained implementation beyond the COVID-19 pandemic. Highlights: Telehealth implementation can augment cancer care, as in COVID-19. More is known about telehealth reach & implementation than adoption & maintenance. Patient-centredness, professional-led & positive perceptions enable implementation. Discomfort with technology & limited infrastructure hinder implementation. Tailored interventions are needed to improve reach for diverse populations.